A New Agglomeration Agent for Increasing Leaching Rate Efficiencies - Dan Walker (Society for Mining, Metallurgy & Exploration, 1992)
The success of the heap leaching process for extracting precious metals from low grade ores in many cases depends on successful agglomeration of clay fines. This paper relates the development of a new agglomeration agent, named Leachit, that has demonstrated an ability in some ores to decrease leaching time. Data from a commercial testing laboratory is presented to illustrate a comparison of leaching efficiencies with other agglomerative agents, such as lime and portland cement. Conclusions will point out certain advantages of Leachit to the heap leaching gold recovery industry.